1997
DOI: 10.1136/jnnp.62.3.265
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial outcome of young adults with epilepsy in childhood.

Abstract: Objective-To evaluate social maturation and psychiatric morbidity in young adults treated for epilepsy during their childhood. Methods-Eighty one young adults (43 women, 38 men, mean age 22-3 years) with epilepsy during their childhood were interviewed about their social development and psychiatric symptoms. The results were compared with those from 211 randomly selected controls (106 women, 105 men, mean age 23-2 years). Results-Compared with the controls the patients had more often not succeeded in passing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
85
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 11 publications
8
85
2
1
Order By: Relevance
“…Comparisons were also made with sibling controls, thus greatly reducing potential confounding influences of familial and environmental factors. With these factors in mind, our finding of higher levels of behavioral problems in children who are seizure-free and off medication relative to their sibling control provides further evidence regarding the concerns raised in long-term follow-up studies of newly-diagnosed epilepsy, [12][13][14]21,22 that there are essential comorbidities associated with epilepsy itself that have an impact on the individual independent of seizures and medication.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Comparisons were also made with sibling controls, thus greatly reducing potential confounding influences of familial and environmental factors. With these factors in mind, our finding of higher levels of behavioral problems in children who are seizure-free and off medication relative to their sibling control provides further evidence regarding the concerns raised in long-term follow-up studies of newly-diagnosed epilepsy, [12][13][14]21,22 that there are essential comorbidities associated with epilepsy itself that have an impact on the individual independent of seizures and medication.…”
Section: Discussionmentioning
confidence: 70%
“…Because these recent studies have not yet followed participants into adulthood, it is unclear how persistent these early indications of difficulties are, and whether these difficulties identified at initial diagnosis explain the unexpectedly poor outcomes in adults with childhood epilepsy in remission and no longer under treatment. [12][13][14]21,22 For example, one study reported that problems present at initial diagnosis did not persist a year later. 28 Our assessments were performed in the context of a large prospective community-based study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several epilepsy variables seem to impact on cognition, behavior and academic skills, including age of onset, disease duration, seizure severity, seizure type and antiepileptic drugs 2 . Also, genetic and environmental influences the degree of cognitive impairment, academic, behavioral and social performance in individuals with epilepsy 3,4,5,6 . Executive functions (EF) are a set of cognitive skills that enable the individual performance of voluntary actions to orient goals 7 , encompassing control processes in cognitive, emotional and social areas 8 .…”
mentioning
confidence: 99%
“…Oulu Finland (Kokkonen et al, 1997) This population-based Finnish series began as a prevalence cohort of all noninstitutionalized children with epilepsy (n = 92) born between 1964-67. When these patients were 22 years of age, they were compared with 211 controls from same birth cohort by interview or questionnaire.…”
Section: Large Population-based Long-term Follow-up Studies From Manymentioning
confidence: 99%